EPISTIMOLOGI ALI SYARI’ATI DAN RELEVANSINYA DALAM MEMBANGUN PEMIKIRAN ISLAM SEBAGAI WORLD VIEW - Fidausy, M. Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Ali Syari’ati is a revolusioner profile who has a great role in Islamic thought. He revolutionary power to release people who are oppressed both culturally and politically. This paper analyzes some concepts on human and the history which views from a sociological point of view as the answer of his criticism on Marx's thought. Islam according to Syari'ati is not only concern with spiritual dimension, but also as the ideology of emancipation and liberation. According Syari’ati, the truly Islamic society does not recognize level of class. It is a place for people who lose their right, and who are marginalized, starving, oppressed, and discriminated. The message of Islam is the message of democracy as stated in the Qur'an. Moreover, Syari'ati relies heavily on the belief that Islam as a scientific school of sociology should be functioned as Qur'an to view human, society, and history. He stresses that history is a flow of event which is sustainable.